AGOA: The US—Africa trade dilemma - John Njiraini (Africa Renewal, 2014)
It may seem counter-intuitive to imagine that Africa could make contractual demands on the United States. Yet, there is evidence that in recent times Africa has become more assertive with a newfound confidence. In fact, it appears the continent is at a point in history where it no longer needs the begging bowl whenever its leaders visit Western capitals.